Pengaruh Jenis dan Tingkat Ketebalan Mulsa pada Pertumbuhan dan Hasil Tanaman Stroberi (Fragaria vesca): The Effect of Type and Thickness of Mulch on The Growth and Yield of Strawberry (Fragaria vesca) - Nur Edy Suminarti; Yoskar, Khaira Annisa (Produksi Tanaman, 2023)
Strawberry development targets are limited to highlands, so crop development is directed to dry land. However, the complexity of the obstacles that must be faced is the low level of water availability for plants. Environmental engineering that leads to suppression of water loss needs to be done through the application of mulch. The purpose of this research was to study and determine the effect of the combination of types and thickness of mulch that is appropriate to increase the growth and yield of strawberry plants grown in dry land. This research was conducted in April - July 2021 at the Experimental Garden of Agrotechnopark Universitas Brawijaya in Jatikerto Village, Malang Regency. This study used a Randomized Block Design (RAK) consisting of: P1: No Mulch, P2: Straw Mulch 2 cm thick, P3: Straw Mulch 4 cm thick, P4: Straw Mulch 6 cm thick, P5: Husk Mulch 2 cm thick, P6: Husk Mulch with a thickness of 4 cm, and P7: Mulch with a thickness of 6 cm. Observational data were analyzed using ANOVA at 5% level and BNJ test at 5% level. The results showed that the combination of different types and thickness of mulch gave different effects on the growth and yield of strawberry plants. Rice straw mulch with a thickness of 4 and 6 cm produced fruit weights that were not significantly different, namely 0.48 tons/ha and 0.50 tons/ha. Ha; 92% and 100% higher than without mulch. 11.63% and 16.28% higher than rice straw with a thickness of 2 cm, 6 cm rice husk mulch produced a fruit weight of 0.45 ton/ha; 80% higher, 21.62% and 21.62% higher than without mulch, rice husk mulch with a thickness of 2 cm, and rice husk mulch with a thickness of 4 cm. Keywords: Strawberry, Mulch, Mulch Thickness, dry land.